Boron Removal by Adsorption onto Different Oxides (Journal of Engineering, 2013)
A research was conducted to determine the feasibility of using adsorption process to remove boron from aqueous solutions using batch technique. Three adsorbent materials; magnesium, aluminum and iron oxide were investigated to find their abilities for boron removal. The effects of operational parameters on boron removal efficiency for each material were determined.The experimental results revealed that maximum boron removal was achieved at pH 9.5 for magnesium oxide and 8 for aluminum and iron oxide. The percentage of boron adsorbed onto magnesium,aluminum and iron oxide reaches up to 90, 42.5 and 41.5% respectively under appropriate conditions. Boron concentration in effluent water after adsorption via magnesium oxide comply with the allowable concentration according to WHO and the Iraqi drinking water guidelines, i.e. below 0.5 mg/l. Aluminum and iron oxide yield effluent water with boron concentration more than allowable limits. Accordingly,magnesium oxide is more suitable as adsorbent for boron removal from water; for its high adsorbent capacity and high removal ability for boron compared with aluminum and iron oxide.